2022
DOI: 10.1007/s10567-022-00385-5
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Mental Health in Parents of Young Children Using eHealth Interventions: A Systematic Review and Meta-analysis

Abstract: Parent stress and mental health problems negatively impact early child development. This study aimed to systematically review and meta-analyze the effect of eHealth interventions on parent stress and mental health outcomes, and identify family- and program-level factors that may moderate treatment effects. A search of PsycINFO, Medline, CINAHL, Cochrane and Embase databases was conducted from their inception dates to July 2020. English-language controlled and open trials were included if they reported: (a) adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 100 publications
2
10
0
Order By: Relevance
“…The discrepancy between the linear mixed modeling and clinical significance results for anxiety may reflect the large point reduction required for the GAD-7. Nonetheless, the pattern of change for the BEAM program aligns with meta-analyses indicating larger effects of digital interventions for anxiety than for depression or parenting stress among parents of young children (25). Together this evidence suggests that parental anxiety may be more responsive to digital health interventions, whereas the cyclical nature of depression and related anhedonia may impede improvement and motivation to engage in a treatment with limited clinical contact.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…The discrepancy between the linear mixed modeling and clinical significance results for anxiety may reflect the large point reduction required for the GAD-7. Nonetheless, the pattern of change for the BEAM program aligns with meta-analyses indicating larger effects of digital interventions for anxiety than for depression or parenting stress among parents of young children (25). Together this evidence suggests that parental anxiety may be more responsive to digital health interventions, whereas the cyclical nature of depression and related anhedonia may impede improvement and motivation to engage in a treatment with limited clinical contact.…”
Section: Discussionsupporting
confidence: 53%
“…In terms of acceptability, the MAUQ findings in the current study indicated slightly lower usability than those for a similar App prototype which targeted parent feeding practices with their infants and toddlers (71). Although engagement and attrition in the BEAM program was comparable to other digital interventions that target parent mental health, parenting skills, or child behavior (25), the lower rate of retention in the intervention compared to the control group may suggest program feasibility issues. Indeed, feasibility challenges in the design process and budget available (as is the case with almost any grant-based project) resulted in a non-optimal digital health platform, which may have impacted user experience, engagement, and ultimately mental health.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Families with low incomes in the United States ( N = 89) participated in a pilot study of an internet-based parenting program and 74% were retained at one month; participants received cash honoraria at appointments (McGoron et al, 2018), but additional retention strategies were not described. In a meta-analysis of 37 studies on eHealth interventions for parents of children aged 1–5 years, 21 (55%) studies reported <20% attrition (MacKinnon et al, 2022); study retention strategies were not a focus of this review paper. Overall, digital research and programs may improve retention in parenting research, but without other strategies they do not appear to provide a panacea for high attrition.…”
Section: Recruitment and Retention Of Families Experiencing Vulnerabi...mentioning
confidence: 99%
“…Currently, there is limited literature on the virtual delivery of whole family work using the LTP and RFP in terms of implementation, feasibility, and acceptability. Although several play‐based interventions for dyads have transitioned to virtual care using VTC (Gurwitch et al., 2020; MacKinnon et al., 2022) and evidence has progressed on efficacy and enhanced access to mental health services for families with infants and young children (McLean et al., 2021; Sossong et al., 2019), there is a pressing need for more research in this area. This is essential to ensure effective delivery of evidence‐based interventions with the very young that incorporate both coparents and siblings.…”
Section: Introductionmentioning
confidence: 99%